Red Imported Fire Ants and Their Impacts on Wildlife - Emma Willcox; William M. Giuliano (EDIS)
Two species of fire ant are found in Florida, the notorious red imported fire ant (RIFA; Solenopsis invicta; Figure 1) and the less common native fire ant (Solenopsis geminata). This document is WEC 207 and one of a series of the Department of Wildlife Ecology and Conservation, UF/IFAS Extension. First published: April 2006.